Testing immediate and retention effects of acoustic feedback on the boat motion in high-performance rowing - Schaffert, N.; Mattes, K. (Journal of Human Sport & Exercise, 2014)
Evidence exists, that rhythmic information, provided audibly, supports the timing of movement-execution subliminally. This study aimed to test immediate effects of acoustic feedback (AF) on mean boat speed during on-water rowing training with elite athletes in two squad-levels and to observe the retention of effects. 20 athletes (14 seniors, age 22.6 ± 1.6 years, body mass 93.1 ± 9.8 kg, body height 192.5 ± 3.3 cm; 6 juniors, age 17.5 ± 0.2 years, body mass 85.0 ± 7.4 kg, body height 189.3 ± 8.8 cm) of the German National Rowing Team in 8 boats (small and big boats) participated in the study. Boat acceleration and distance travelled were measured with Sofirow. The boat`s acceleration-time trace was converted online into AF and presented to the athletes via speakers. Repeated measures within-subjects factorial ANOVA showed significantly increased mean boat speed with AF compared to baseline for both squad-levels (P < 0.01) as well as for the retention-test compared to pre-test (P < 0.01). Intra-cyclical analysis revealed significant changes in the acceleration-time traces. Athletes perceived AF as supportive for training, providing functional information about the boat-run, independently from vision. The concept was integrated into the final-preparation for the World Championships.